2019
DOI: 10.7150/thno.32363
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived nanovesicles promote lung distribution of the therapeutic nanovector through repression of Kupffer cell-mediated phagocytosis

Abstract: Tumor-derived nanovesicles have been widely used as a biomarker or therapeutic target in various tumor types. However, these nanovesicles have limited use in therapy due to the risk of advancing tumor development. Methods : Exosome-like nanovesicles (ENVs) were developed from metastatic breast cancer 4T1 cells-derived exosomes. The distribution of ENVs and their impact on macrophage-mediated phagocytosis were evaluated. The effect of ENVs pretreatment on anti-lung metastasis therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…It is suggested that tumor cell-derived EVs (TEVs), especially autologous TEVs, carry tumor antigen repertoires, costimulatory molecules, and DNA fragments similar to their parental cells (Qiu et al, 2019;Rahbarghazi et al, 2019). This nature could elicit a potent T cell-dependent anti-tumor immune response and achieve therapeutic effects in mouse models of melanoma (Mannavola et al, 2019), hepatocellular carcinoma (Moris et al, 2017), and colon carcinoma (Teng et al, 2017).…”
Section: Tumor Cellsmentioning
confidence: 99%
“…It is suggested that tumor cell-derived EVs (TEVs), especially autologous TEVs, carry tumor antigen repertoires, costimulatory molecules, and DNA fragments similar to their parental cells (Qiu et al, 2019;Rahbarghazi et al, 2019). This nature could elicit a potent T cell-dependent anti-tumor immune response and achieve therapeutic effects in mouse models of melanoma (Mannavola et al, 2019), hepatocellular carcinoma (Moris et al, 2017), and colon carcinoma (Teng et al, 2017).…”
Section: Tumor Cellsmentioning
confidence: 99%
“…As naturally derived nanovesicles, exosomes efficiently deliver exogenous RNAs (siRNAs and miRNAs) to target tissues/cells in vivo 3. Despite multiple advantages over existing synthetic systems, such as less immunogenicity and higher affinity, exosomes suffer from the drawback of endocytosis by the mononuclear phagocyte system (MPS), such as in the liver and spleen, limiting their distribution in other tissues like heart 4. Due to the high prevalence of heart disease, there is a great demand for improving the cardiomyocyte-specific delivery of exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Even though EVs have various advantages compared to existing delivery systems, such as lower immunogenicity and higher affinity, their distribution to the heart is limited by rapid clearance from the blood by the MPS and subsequent accumulation in the liver and spleen 154 . The plasma half-life of EVs is only 70-80 min 155 , 156 .…”
Section: Targeted Delivery Of Therapeutic Extracellular Vesicles In Hmentioning
confidence: 99%